FERTILIZAÃ‡ÃƒO FOLIAR DE SORGO COM MANIPUEIRA (EXTRATO LÃQUIDO DAS RAÃZES DE MANDIOCA) - Ponte, J. JÃºlio da; AragÃ£o, M. L.; Silveira Filho, J.; Andrade, N. C. (REVISTA DE AGRICULTURA, 2015)
FERTILIZAÃ‡ÃƒO FOLIAR DE SORGO COM MANIPUEIRA (EXTRATO LÃQUIDO DAS RAÃZES DE MANDIOCA)